1993
DOI: 10.1288/00005537-199307000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Direct application of basic fibroblast growth factor improves tympanic membrane perforation healing

Abstract: Topical application of basic fibroblast growth factor (b-FGF) on tympanic membrane (TM) perforations was studied in guinea pigs. One-millimeter simple round TM perforations or 2-mm TM perforations with medially flapped borders were performed. Either b-FGF or placebo was instilled in each ear on the day of surgery and daily thereafter. Treatment was applied either directly to the perforation or to a Gelfoam pledget over the defect. When no scaffolding material was interposed, b-FGF induced a faster healing resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 17 publications
3
59
0
2
Order By: Relevance
“…Fina et al [13] take the view that while treating traumatic perforation of the tympanic membrane, the gelatin sponge patching technique can be used to increase the formation of granulation tissue at the perforation edge. This is because the granulation tissue is rich in capillary vessels, thereby helping the process of perforation healing.…”
Section: Discussionmentioning
confidence: 99%
“…Fina et al [13] take the view that while treating traumatic perforation of the tympanic membrane, the gelatin sponge patching technique can be used to increase the formation of granulation tissue at the perforation edge. This is because the granulation tissue is rich in capillary vessels, thereby helping the process of perforation healing.…”
Section: Discussionmentioning
confidence: 99%
“…All treatment and con trol ears achieved complete closure, and microscopic find ings revealed healed tympanic membranes to be of similar thickness in both groups [10], Another study found im proved healing rates using FGF in the treatment of small, acute guinea pig tympanic membrane perforations. FGFtreated eardrums had accelerated connective tissue prolif eration which was felt to facilitate epidermal migration [11]. A third study addressed the repair of chronic, large perforations using a chinchilla model.…”
Section: Discussionmentioning
confidence: 99%
“…With such a high healing rate in the control group, it is difficult to compare the benefit of treatment in small sam ple groups. The thermal-myringotomy loop method of perforation as utilized in several other animal models may facilitate the creation of a persistent perforation [2,5,11], However, this mode of injury may change the physi ology of the healing mechanism which is being investi gated. In the guinea pig model, fibrin glue does not appear to increase cellular proliferation following myringoplasty and provided no benefit over the control treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Be son ders ge eig net schei nen der epider ma le Wachs tums fak tor ("epi der mal grow th fac tor", EGF) und der ba si sche Fibro blas ten wachs tums fak tor ("ba sic fi broblast grow th fac tor", bFGF) zu sein [13].All ge mein gilt die Ent wick lung ei nes geeig ne ten Frei set zungs sys tems als ei nes der ent schei den den noch zu lö sen den Pro b leme bei der An wen dung von Wachs tumsfak to ren [5,9]. Dies zeigt sich be son ders deut lich am Bei spiel des EGF, des sen Einsatz we gen des pri mär epi the lia len Verschlus ses ei ner Trom mel fell per fo ra ti on beson ders sinn voll er scheint.…”
unclassified